Listening to First Generation College Students in Engineering: Implications for Libraries & Information Literacy - Emily Dommermuth; Linds W. Roberts (Communications in Information Literacy, 2022)
First-generation college students (FGCS) in engineering bring a wealth of knowledge to their academic and social experiences in higher education, in contrast to deficit-based narratives that students are underprepared. By listening to FGCS’ own experiences navigating higher education and using information literacy in their project-based work, librarians and educators can better understand students’ funds of knowledge, social capital, and identities, as well as the institutional barriers that must be removed. This paper shares interview findings with (n = 11) FGCS and suggests implications for professional practice that are relevant to information literacy for design, project-based, or practitioner focused disciplines.